计算:
2008+2007×2009 |
2008×2009-1 |
+
2009+2008×2010 |
2009×2010-1 |
+
2010+2009×2011 |
2010×2011-1 |
+
2011+2010×2012 |
2011×2012-1 |
= ___ .
人气:105 ℃ 时间:2019-08-19 01:33:42
解答
2008+2007×2009 |
2008×2009-1 |
+
2009+2008×2010 |
2009×2010-1 |
+
2010+2009×2011 |
2010×2011-1 |
+
2011+2010×2012 |
2011×2012-1 |
=
2008+2007×2009 |
2007×2009+2009-1 |
+
2009+2008×2010 |
2008×2010+2010-1 |
+
2010+2009×2011 |
2009×2011+2011-1 |
+
2011+2010×2012 |
2010×2012+2012-1 |
,
=
2008+2007×2009 |
2008+2007×2009 |
+
2009+2008×2010 |
2009+2008×2010 |
+
2010+2009×2011 |
2010+2009×2011 |
+
2011+2010×2012 |
2011+2010×2012 |
,
=1+1+1+1,
=4.
推荐
猜你喜欢